Space to grow. Working principles for child-friendly cities. - Eisenberg, Tara; Gold, Riley (Steiner, 2018)
This essay briefly explains the importance of supporting our youngest city residents. It then offers a series of working principles for achieving a more playful, supportive and friendly city, in which more children and caregivers can participate in public life, drafted by Gehl Institute in collaboration with the Bernard van Leer Foundation.
Keywords: Stadtentwicklung; Kind; Nutzerbedürfnis; Partizipation; Planungsziel; Öffentlicher Raum; Zielgruppe; Kinderfreundliche Stadt; Raumnutzung; Aneignung